Apple Inc.: a marketing analysis case study - Nagamia, Namira Kausar (My University, 2015)
Apple has been at the leading edge in the electronics industry ever since the launch of its first product. In addition to showing good market and financial performance the company has also demonstrated socially responsible behavior towards its employees and the environment. This case study exemplifies how the principles of environmental scanning and market segmentation can be systematically applied to Apple’s various product lines. Specifically, the influence of economic and competitive factors on Apple’s marketing has been discussed. Further, income levels (demographic) and life stage (socio-cultural) factors in order to study consumer behavior have been applied to arrive at key market segments for the company’s products such as IPods, IPads, IPhones, and MacBook/IMac.
Keywords: environmental scanning; market segmentation; Apple